Representasi Keluarga Jawa Dalam Film Jokowi - Hudoyo, Sapto; Mulia, Prajanata Bagiananda (Capture : Jurnal Seni Media Rekam, 2014)
Javanese family is smallest scope of Javanese society. Social conditions of thefamily can be represented in various ways through various media, such as through themedium of movie. Movie entitled Jokowi is a biopic film with Javanese background.The film tells the struggle of life in chronological order. The film depicts a life conditionsof character with the Javanese family, set in the period of 1960 through 2012. TheJavanese family concept from literature books that according with time frames or yearsof the story, is used as references for a family reading of social interaction that appearsfrom the primary data, they are pieces of movie scenes. This study aims to determinehow the Javanese family represented through the Jokowi film. The method used in thisresearch is descriptive qualitative method, with approach a representation theory ofStuart Hall as the reading method. Representation approach is used to posit the film asa medium that can construct the meaning through language (constructionist). So, it canappears 6 selected sequences, contains scenes which may represent a social life ofJavanese family inside the film. The results of this study showed a nearly balanced,which appears three equations, two shifts, and one difference. Equations that appearare: (1) social relations childhood in a family through the closeness between father andson was a toddler; (2) the status of teenage boys who attend school; and (3) a patternof domestic cooperation through the division of labor. Then, a shift that appears are: (1)the social status of the family through a way of having a baby; (2) the role of parentsthrough of punishing the child after a fight. In addition, one significant difference thatappear is the closeness of father and son through the way of greeting each other.Keywords: family, Jawa, representation, and Jokowi